A biomimetic three-layered fibrin gel/PLLA nanofibers composite as a potential scaffold for articular cartilage tissue engineering application. (1st September 2022) - Riazi Moghadam, Roozbeh; Keshvari, Hamid; Imani, Rana; Nazarpak, Masoumeh Haghbin
Abstract: Developing an engineered scaffold inspired by structural features of healthy articular cartilage (AC) has attracted much attention. In this study, the design and fabrication of a three-layered fiber/hydrogel scaffold in which each layer replicates the organization of a pertinent layer of AC tissue is aimed. To this end, electrospun poly-L-lactic acid (PLLA) nanofibers are prepared and fragmented into nano/micro cylinders via aminolysis. Three-layers of the scaffold, a fibrin coated fibrous layer, a fibrin gel (FG) layer incorporating chopped fibers and a FG embedding cylindrical aligned fibrous mat perpendicular to articulating surface, respectively served as an upper, middle and bottom layers, are prepared. The layers' physicomechanical characteristics are comprehensively evaluated. Results show that optimized electrospinning set up results in the smallest fibers diameter of 367 ± 317 nm and successful aminolysis provides amine-functionalized chopped nanofibers with a mean length of 1.46 ± 0.9 µm. Static mechanical analysis of the layers demonstrates that tensile Young's modulus of the upper layer is 152 ± 17 MPa while compressive moduli of the middle and bottom layers are 9.8 ± 3.8 and 25.3 ± 5.2 KPa, respectively and the compressive modulus of three-layered scaffold is 13.7 ± 2.5 KPa. Assessing mechanical parameters under dynamic loading also shows that adding fibrous part in the composite scaffold layers enhances viscoelastic behavior of FG. Also, incorporation of 0.25% chopped fibers into the fibrin matrix notably enhances the equilibrium water content; however, it increases in-vitro weigh loss rate from 6% to 10.5% during a seven-day period. Cytocompatibility analysis confirms that all layers possess acceptable cytocompatibility. In a conclusion, the designed three-layered composite structure successfully mimics the physicomechanical as well as microstructural features of AC and could be suggested as a potential scaffold for this tissue regeneration.